Pengaruh Citra Merek, Word Of Mouth, Dan Harga Terhadap Keputusan Pembelian Produk Emina Di Universitas Simalungun - Nida Shafiyyah; Rizka Praswalita; Yan Lihardo F. Saragih; Duwi Anggela (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The aim of the research is to make decision knowledge in purchasing emina products by students at Simalungun University. This study took the population at the Faculty of Economics, the sample used was 25 respondents. By using a probability sampling technique with a simple random sampling type. The results of the analysis carried out using the simultaneous test (f) concluded that brand image, word of mouth, and price have a simultaneous and significant influence on purchasing decisions. With simultaneous F results, a result of 2,157 is obtained with a level of 0.000